A Teaching Strategies to Enhance Students’ Creativity in English Profession Subject during the Covid-19 Pandemic - Diani Nurhajati (Journal of Development Research, 2021)
During the Covid-19 pandemic, the learning process must be carried on from home. In fact, all of the university graduates should be equipped with a number skills needed to face the Industrial Revolution 4.0. Therefore, lecturers are expected to find the solution to train the skills, including creativity. One of the solutions is selecting the right teaching strategy. This research was carried out to answer the questions: “What are the teaching strategies employed by the lecturer English Profession to promote creativity?” and “How do the strategies enhance the students’ creativity?” This descriptive qualitative study took 60 students as the subjects. They were the students who took English Profession Subject at the Elementary School Education, University of Nusantara PGRI Kediri. The techniques of collecting data were observation checklist and questionnaire. The findings of the research show that the lecturer employed Project Based Learning in which the students were assigned to create some projects, namely video, game manual, and English book for elementary school students.